2013
DOI: 10.4172/2155-6156.1000244
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Test to Detect Stress Induced Ischemic Heart Disease in Type 2 Diabetes Mellitus Patients Asymptomatic for CAD: A Hospital Based Cross-sectional Study in Rural Population of Central India

Abstract: Background: Progressive Coronary Artery Disease (CAD) remains asymptomatic in many cases of type 2 diabetes mellitus (DM) and this makes diagnosis difficult. Routine screening of type 2 DM for silent ischemia with electrocardiography (ECG) remains controversial as majority of patients present with normal ECG. This study aims at using Treadmill Test (TMT) to determine the percentage of ischemic heart disease (IHD) in diabetic patients, having normal resting ECG and 2D Echo, in a rural set up of Central India. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…The mean age study subjects were 54.7 years. Similar results were seen by Swaminathan K et al 13 (52.3 ± 5.6) and Lavekar AS et al 14 (53.56 ± 7.41). This may reflect the health-seeking behaviour of study subjects after the age of 40 years.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mean age study subjects were 54.7 years. Similar results were seen by Swaminathan K et al 13 (52.3 ± 5.6) and Lavekar AS et al 14 (53.56 ± 7.41). This may reflect the health-seeking behaviour of study subjects after the age of 40 years.…”
Section: Discussionsupporting
confidence: 88%
“…A strong association between poor glycaemic control and inducible ischaemia has been observed by Lavekar AS et al The mean value of FBS in the present study is 141 mg/dl, which is closer to mean observed in Khanapure SP et al In the present study, the mean BMI of study subjects was 24.84 kg/m 2 . Similarly, in the study involving the rural population of Maharashtra by Lavekar AS et al 14 the mean BMI of the subjects were 25.62 kg/m 2 . However, in the study by Khanapure SP et al involving an urban population of Karnataka the mean BMI of the subjects were 30.44 kg/m 2 which is higher compared to the present study.…”
Section: Discussionmentioning
confidence: 73%
“…Routine screening of type 2 diabetics for asymptomatic coronary artery disease with ECG remains controversial, as majority of them present with normal ECG(American Diabetes Association 2010). However, progressive coronary artery disease remains asymptomatic in many cases of type 2 diabetes and this makes diagnosis difficult at proper time Many studies have been published showing relationship between DM and silent ischemia (Lavekar and Salkar 2013).…”
Section: Silent Ischemiamentioning
confidence: 99%
“…Additionally, screening asymptomaticT2DMpatients with myocardial perfusion imaging may produce a significant number of high-risk scans (Cosson et al, 2011;Kumar 2014;Lavekar and Salkar 2013;Upchurch and Barrett 2012). One retrospective study suggested that some of these scans will uncover patients with angiographic findings that merit surgical revascularization (left main, three-vessel, and/or proximal left anterior descending) (Rajagopalan et al, 2005), possibly leading to better survival with coronary artery bypass grafting (CABG) over medical therapy.…”
Section: Silent Ischemiamentioning
confidence: 99%
“…Coronary Artery Disease (CAD) is multifactorial in aetiology and has several important risk factors, out of which diabetes is one of the important modifiable risk factor. 5 Coronary artery disease is more common in diabetic population, but can be asymptomatic in many patients and may present with sudden death, myocardial infarction, arrhythmia, silent myocardial ischaemia or heart failure. Early detection of asymptomatic coronary artery disease in Type 2 Diabetes may prevent catastrophic cardiac events.…”
Section: Introductionmentioning
confidence: 99%